Time Series Analysis and Applications 2018
DOI: 10.5772/intechopen.71041
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Worry and Fear: Quantifying the Mind Using EKG Time Series Analysis

Abstract: We analyse the heartbeat interval time series in this chapter. Our time series analysis concepts and techniques have been reported previously, for example, in the Intech Book chapter. Here, we would like to introduce how it works by presenting typical examples. The techniques can distinguish between healthy, sick and stressful hearts. All data were obtained by us from natural heartbeat data. Therefore, we have notes behind data, especially about behavioural psychological observations. Results of analysis are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Here, the brain does not concentrate on meal, and the scaling exponent was not noticeably altered. The previous report also supports this interpretation of "having meal mDFA" (see Figure 14 of previous publication [19]). If individuals were interested in not so meal but conversation, we found that the scaling exponent did not decrease significantly.…”
Section: Mdfa During Working Eating and Doing Exercisesupporting
confidence: 68%
See 1 more Smart Citation
“…Here, the brain does not concentrate on meal, and the scaling exponent was not noticeably altered. The previous report also supports this interpretation of "having meal mDFA" (see Figure 14 of previous publication [19]). If individuals were interested in not so meal but conversation, we found that the scaling exponent did not decrease significantly.…”
Section: Mdfa During Working Eating and Doing Exercisesupporting
confidence: 68%
“…In conclusion, the best window size, that is, the domain 30 < l < 270, ensures that mDFA gives a reliable and satisfactory useful scaling index, as shown in the results section below. Our mind might be quantified by the scaling index [18,19]. We can peer into the mind through a window.…”
Section: Mdfa: Root Mean Square and Box Sizementioning
confidence: 99%
“…The mDFA program was made by a former master student Tanaka [7] mDFA results are reproducible and consistent. We found stratification phenomena that provide evidence for the quantitative measure SI links to various physiological phenomena in a one-to-one manner [1,7,[10][11][12]. Arrhythmic heartbeat decreases SI [11].…”
Section: Si: Reproducibilitymentioning
confidence: 59%
“…Alternans (harbinger of death rhythm) decreases SI [7]. Anxiety, fear, and worry decrease SI [10]. University president, vice president, president-secretary, and dean professor all have a low SI [1] but teaching-only professors have a healthy SI (SI = ~1.0) [1].…”
Section: Si: Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation